2022
DOI: 10.3389/fpubh.2022.866324
|View full text |Cite
|
Sign up to set email alerts
|

How Two-Child Policy Affects China's Energy Consumption: The Mediating Role of Lifestyle

Abstract: BackgroundExisting literature believed that the birth control policy affects energy consumption through the change in population size, but ignored the changes in people's lifestyle. This may mislead the government's policy-making about population and energy consumption.MethodThis article proposed a Population-Lifestyle-Energy (PLE) model to provide new insights into how birth control policy affects energy consumption if the changes in people's lifestyle are considered. The ProFamy software is used to forecast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that conception with the help of ART may result in a higher rate of missed abortions and embryonic chromosome abnormalities ( Askerov, 2016 ; Li et al, 2018b ), which is consistent with our study. After the implementation of Chinese two-child and three-child policies ( Chen et al, 2022 ; Long et al, 2022 ), many women who cannot get pregnant naturally due to previous tubal ligation or advanced age get pregnant by ART. Further research is necessary to clarify the relationship between ART and embryonic chromosome abnormalities to promote the development of ART technology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that conception with the help of ART may result in a higher rate of missed abortions and embryonic chromosome abnormalities ( Askerov, 2016 ; Li et al, 2018b ), which is consistent with our study. After the implementation of Chinese two-child and three-child policies ( Chen et al, 2022 ; Long et al, 2022 ), many women who cannot get pregnant naturally due to previous tubal ligation or advanced age get pregnant by ART. Further research is necessary to clarify the relationship between ART and embryonic chromosome abnormalities to promote the development of ART technology.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing research on fertility policy has combined with medicine [ 9 ], finance [ 10 ], and other disciplines to explore the impact of policy implementation on various fields, and its sociology has focused mainly on fertility policy [ 11 ], problems [ 12 ], and institutional responses [ 13 ] through traditional statistical data. Demography measures the fertility willingness of a certain population group [ 14 ], focusing on fertility macro trends [ 15 ] and fertility prediction [ 16 ].…”
Section: Introductionmentioning
confidence: 99%